Factors associated with extubation failure in the intensive care unit patients after spontaneous breathing trial - Niraj Kumar Keyal; Roshana Amatya; Gentle Sunder Shrestha; Saurabh Pradhan; Krishna Kumar Agrawal; Hem Raj Paneru (Wolters Kluwer Medknow Publications, 2020)
Introduction: Extubation failure is associated with high mortality and poor outcome of patients. Aims: This study was conducted to assess the factors associated with extubation failure in the intensive care unit (ICU) patients planned for extubation. Settings and Design: It was a prospective observation study conducted in all patients aged >18 years admitted in the ICU of a tertiary care hospital. Subjects and Methods: It was done on 108 patients who were planned for extubation. Patients were assessed by an intensivist clinically and decided whether a patient can be extubated on clinical grounds. Spontaneous breathing trial (SBT) was done for 2 h by T-piece in patients who met clinical and objective criteria. Arterial blood gas (ABG) was done in all patients who successfully completed SBT. Patients with successful SBT and acceptable ABG were extubated. Patients were observed for 48 h for extubation failure, and the reason for reintubation was recorded. Statistical Analysis Used: Independent Student's t-test and Chi-square test were used for data analysis. Results: Of 108 patients who passed the SBT, 96 (88.88%) patients had acceptable ABG and were extubated. 85 (88%) underwent successful extubation and 11 (12%) underwent unsuccessful extubation. Duration of mechanical ventilation (MV) and chronic obstructive airway disease was a risk factor associated with extubation failure. Conclusion: Duration of MV of >2 days and chronic obstructive pulmonary disease were identified as independent risk factors for extubation failure.